Early diagnosis and therapy of Chlamydia psittaci pneumonia: insights from chest CT, tNGS, and omadacycline in 34 cases - Qiuting Jiang; Xiaoli Zhao; Yuan Zhu; Xinmin Zhu; Shaohua Hu; Huajuan Zhou (Frontiers in Medicine, 2026)
Objective This study retrospectively analyzed the clinical characteristics and management strategies of 34 patients with Chlamydia psittaci pneumonia. We aimed to evaluate the diagnostic value of subpleural-predominant pulmonary CT manifestations combined with bronchoalveolar lavage fluid targeted next-generation sequencing (tNGS), and to assess the clinical efficacy and therapeutic advantages of omadacycline in this patient cohort. Methods Clinical data were retrospectively collected from patients diagnosed with C. psittaci pneumonia by tNGS/PCR, from January 2024 to April 2026. Demographic characteristics, epidemiological history, clinical manifestations, laboratory findings, imaging features, treatment regimens, and clinical outcomes were analyzed. Results A total of 34 patients were enrolled. Twenty-four patients (70.6%) had a history of close contact with birds or avian excreta. All patients developed fever, with a mean maximum body temperature of 39.6 ± 0.5°C, and fever was the predominant initial symptom in 29 patients (85.3%). Laboratory findings were characterized by elevated C-reactive protein levels in all patients. Chest imaging predominantly showed subpleural lesions presenting as consolidation, and the typical reverse halo sign was observed in 5 patients (14.7%). 30 patients diagnosed by tNGS and 4 diagnosed by PCR. The median C. psittaci sequence count detected by tNGS in bronchoalveolar lavage fluid (BALF) was 3,773.5 reads (IQR,588.5–11,856.0). Compared with non-omadacycline regimens, omadacycline was associated with a shorter time to defervescence (1.0 vs. 3.0 days, p < 0.001) and a greater reduction in C-reactive protein levels after 5 days of treatment (143.6 ± 63.2 mg/L vs. 87.4 ± 57.9 mg/L, p < 0.05), Notably, omadacycline demonstrated considerable clinical efficacy even in patients who had failed initial quinolone therapy. All patients improved and were discharged after effective antimicrobial therapy. Conclusion C. psittaci pneumonia may occur without a clear epidemiological history and typically presents with high fever and nonspecific laboratory abnormalities. Subpleural consolidation and the reverse halo sign on chest imaging may provide important diagnostic clues. BALF tNGS is valuable for the early identification of C. psittaci infection, and omadacycline may be an effective therapeutic option, particularly in patients with persistent fever after quinolone therapy.